2014
DOI: 10.1128/jvi.03422-13
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry Reveals that H5N1 Vaccination Elicits Cross-Reactive Stem-Directed Antibodies from Multiple Ig Heavy-Chain Lineages

Abstract: An understanding of the antigen-specific B-cell response to the influenza virus hemagglutinin (HA) is critical to the development of universal influenza vaccines, but it has not been possible to examine these cells directly because HA binds to sialic acid (SA) on most cell types. Here, we use structure-based modification of HA to isolate HA-specific B cells by flow cytometry and characterize the features of HA stem antibodies (Abs) required for their development. Incorporation of a previously described mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
309
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(318 citation statements)
references
References 35 publications
9
309
0
Order By: Relevance
“…This mutation has previously been shown to have the greatest impact in lowering sialic acid binding activity (34,35), although it is important to keep in mind that the receptor-binding domain is composed of several residues that contribute to receptor recognition, including W166, analysis. An anti-mouse F(ab′) 2 -specific secondary antibody conjugated to HRP was used to visualized the antibody isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This mutation has previously been shown to have the greatest impact in lowering sialic acid binding activity (34,35), although it is important to keep in mind that the receptor-binding domain is composed of several residues that contribute to receptor recognition, including W166, analysis. An anti-mouse F(ab′) 2 -specific secondary antibody conjugated to HRP was used to visualized the antibody isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…The coding regions of the FLAG-tagged HAs were subsequently subcloned into the ambisense expression plasmid pDZ (55). The HA of A/California/04/09 (H1) virus with a defective receptor-binding site (Y108F) was generated by mutating the tyrosine at site 108 (methionine, residue 1) into a phenylalanine and was subcloned into pDZ (34).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry-based probes have recently been developed or optimized to evaluate memory B cells specific to antigens of common vaccines, including influenza (38) and tetanus (39). We took advantage of these highly specific probes to compare IgG + B cell reactivities against HIV and non-HIV antigens among 12 HIV-viremic individuals selected on the basis of their immunization histories (see details in Methods).…”
Section: Hiv-specific B Cell Responses In Early and Chronically Hiv-imentioning
confidence: 99%
“…We have previously confirmed that influenza virus-specific plasmablasts are induced transiently in large number in the peripheral blood during the first week after vaccination with inactivated former seasonal H1N1 and H1N1pdm09 viruses and the frequency of influenza virus-specific plasmablasts significantly correlated with the level of neutralizing antibody response (16)(17)(18) Binding of recombinant HA to transmembrane Ig G1. In these experiments, the HA molecules did not have any mutations to abolish sialic acid binding, as described by Whittle et al (19). In contrast to Whittle's method, in which the trimeric HA was combined in excess with streptavidin to form oligomers prior to staining, we stained sequentially with hemagglutinin followed by ExtrAvidin.…”
Section: Introductionmentioning
confidence: 99%